LEADING TRENDS IN THE MODERN UKRAINIAN LANDSCAPE - I.H. Brizhata (Academy of Cognitive and Natural Sciences, 2022)
The main tendencies of the development of Ukrainian landscape are dealt with in the article. The priorities of the stylistics' genre, the system of the expressive means are underlined on the basis of the analysis of the work of the modem craftsman.